Interactional functions and students’ perceptions of teacher talk : teacher questions and requests in adolescent science classrooms in Iceland - Wöll, Christoph, 1980- (2018)
The purpose of this qualitative study was to explore interactional characteristics of teachers’ questions and requests. This object was approached through pragmatically analysing teacher questions and requests in three adolescent science classrooms in Iceland. Participants’ views were added to the analysis through separate interviews with teachers and students, which were held after lessons had been video recorded and the pragmatic analysis had been conducted. During the interviews participants’ conceptions of teacher talk in general and of episodes recorded during lessons were explored. The pragmatic analysis, which is rooted in speech act theory and politeness theory, shows that teachers commonly use certain strategies to mitigate the directness of questions that target knowledge display of students and that they make requests of students in varied ways utilising almost the whole spectrum of request strategies. Differences between teachers relate to the frequency with which they mitigate their display questions and requests. These differences are traced to different interactional styles and to the fact that the sociological variables of distance and students’ power are larger in one classroom than in the other two. Further noticeable differences between teachers regard whether or not they use topical questions to control student behaviour and whether they predominantly ask the whole class or individual students. The majority of students report that they experience fear of embarrassment in their peers’ eyes when faced with display questions and that this causes teacher questions to have a negative impact on their participation. Teachers are shown to be differently aware of the fact that their questions can induce student anxiety or be misunderstood in other ways. These findings encourage the use of talk strategies that make the interactional architecture of adolescent classrooms more transparent in order to minimise the risk that teacher talk becomes the source of misunderstandings and adverse student ...